2004
DOI: 10.1191/0969733004ne662oa
|View full text |Cite
|
Sign up to set email alerts
|

Caring Work, Personal Obligation and Collective Responsibility

Abstract: Studies of workers in health care and the care of older people disclose tensions that emerge partly from their conflicting obligations. They incur some obligations from the personal relationships they have with clients, but these can be at odds with organizational demands and resource constraints. One implication is the need for policies to recognize the importance of allowing workers some discretion in decison making. Another implication may be that sometimes care workers can meet their obligations to clients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Some ED nurses reported active resistance to the target, where nurses refused to move patients who were not seen as clinically ready to leave the ED. This resistance aligns with the existing literature which has found strong support for nurses rejecting targets that did not fit with their beliefs (Wells , Provis & Stack , Bergen & While , Kramer et al . ), and thus contrasts Hunters' ().…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some ED nurses reported active resistance to the target, where nurses refused to move patients who were not seen as clinically ready to leave the ED. This resistance aligns with the existing literature which has found strong support for nurses rejecting targets that did not fit with their beliefs (Wells , Provis & Stack , Bergen & While , Kramer et al . ), and thus contrasts Hunters' ().…”
Section: Discussionsupporting
confidence: 87%
“…However, there has been a dearth of research examining how health professionals use discretion and navigate targets. Research has found that nurses were most likely to follow local guidance and clinical guidelines if they were adequately resourced (Wells ), clear and fit with both local practice, (Bergen & While ) and the nurses' own beliefs (Provis & Stack , Kramer et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The legal criterion of causality between danger and psychiatric disorder may be loosened up at this point in time. So, we suggest some degree of latitude in organizational policy and legal criteria, by which is meant vagueness or open texture in what is required and possible, so as to allow healthcare professionals some discretion in what they can do (Provis & Stack, , p. 10).…”
Section: Overcoming Tensionsmentioning
confidence: 99%
“…Some studies have turned up cases where workers perceive themselves to have responsibilities to clients which they cannot fulfil because of organisational policies or constraints (see e.g. van den Broek 2003, Provis & Stack 2004). We can easily imagine cases where management directions or organisational policies impede teachers from carrying out responsibilities they take themselves to have to students, nurses from carrying out responsibilities they take themselves to have to patients, police officers take themselves to have to members of the public, and so on.…”
Section: Ethics Work and Industrial Relationsmentioning
confidence: 99%